Health related quality of life of infants and children with avoidant restrictive food intake disorder. Issue 4 (7th February 2019) - Krom, Hilde; van der Sluijs Veer, Liesbeth; van Zundert, Suzanne; Otten, Marie‐Anne; Benninga, Marc; Haverman, Lotte; Kindermann, Angelika
Abstract: Objective: The aim of this study was to compare health related quality of life (HRQOL) in infants and children with avoidant restrictive food intake disorder (ARFID) to healthy and chronically ill controls. Method: A cross‐sectional study was conducted in children who meet ARFID criteria at our tertiary care pediatric feeding clinic (September 2014 to July 2016). Before consultation, parents of patients ( n = 100) were asked to complete questionnaires to determine HRQOL: the TNO‐AZL Preschool Children Quality of Life (0–5 years), and "Pediatric Quality of Life Inventory" (6–7 and 8–10 years). HRQOL of ARFID patients was compared to both healthy (0–5 years n = 241; 6–7 years n = 61; 8–10 years n = 192) and chronically ill (0–5 years n = 79; 6–7 years n = 11; 8–10 years n = 26) controls. Results: The prevalence of ARFID was 64%. HRQOL of ARFID patients aged 0–5 years ( n = 37) was significantly lower on 6/12 scales (appetite, lungs, stomach, motor functioning, positive mood and liveliness) compared to healthy controls ( P < .01), and on 4/12 scales (appetite, stomach, motor functioning, and liveliness) compared to chronically ill controls ( P < .01). The ARFID patients scored significantly better on the problem behavior scale compared to healthy and chronically ill controls ( P < .01). ARFID patients aged 6–7 ( n = 9) had significantly lower scores in 3/6 scales (total score, psychosocial health, and school functioning) ( P < .01), and aged 8–10 ( n = 2) had a significantly lower school functioning scale ( P < .01) compared to healthy controls. Conclusion: HRQOL of children with ARFID is decreased on multiple scales. The effect on HRQOL should be incorporated in clinical practice, and clinical studies should add HRQOL as an outcome measure.